Enhancing Smallholder Farmers' Access to Seed of Improved Legume Varieties Through Multi-stakeholder Platforms Learning from the TLIII project Experiences in sub-Saharan Africa and South Asia - Akpo, Essegbemon; Ojiewo, Chris O.; Kapran, Issoufou; Omoigui, Lucky O.; Diama, Agathe; Varshney, Rajeev K.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2021)
This open access book shares the experiences of Tropical Legumes III (TLIII) project in facilitating access to seed of improved legume varieties to smallholder farmers through innovation platforms. It highlights practices and guiding principles implemented in eight developing countries of sub-Saharan Africa and South Asia. This book details key processes that respective teams employed to create an innovation space that delivers seed, other inputs, knowledge and financial services to agricultural communities and most importantly, the underserved farmers in remote areas of the drylands. It offers valuable insights into the pathway to establishing, promoting and operating innovation platforms to enhance the performance and competitiveness of legume crops$1 (Bvalue chains, and addresses critical issues that must be considered to make innovation platforms more sustainable and attractive to beneficiaries. The book offers a wealth of practical insights for development workers, technicalstaff, and project managers. This publication is all about TLIII community of practice. It will definitely inspire other development workers and scientists to share their own experiences for others to learn from.s
Chapter 1. General context of smallholder farmers$1 (Baccess to seed of improved legume varieties and innovation platform perspectives -- Chapter 2. Groundnut Seed Production and Distribution through Multi-stakeholder Platforms in Southern Region of Tanzania -- Chapter 3. An analysis of groundnut innovation platform achievements in brokering improved varieties to communities in TL III project in Burkina Faso -- Chapter 4. Kolokani groundnut innovation platform activities and achievements through TL III project in Mali -- Chapter 5. Enhancing access to quality seed of improved groundnut varieties through multi-stakeholder platforms in Northern Ghana -- Chapter 6. Impact assessment of developing sustainable and impact-oriented groundnut seed system under the Tropical Legumes (III) project in Northern Nigeria -- Chapter 7. Enhancing chickpea production and productivity through Stakeholders$1 (BInnovation Platform approach in Ethiopia -- Chapter 8. Organized farmers towardschickpea seed self-sufficiency in Bundelkhand region of India -- Chapter 9. Developing sustainable cowpea seed systems for smallholder farmers though innovation platforms in Nigeria: Experience of TL III Project -- Chapter 10. Cowpea seed innovation platform: A hope for small seed producers in Mali -- Chapter 11. Cowpea innovation platform interventions and achievements in TL III project in Burkina Faso -- Chapter 12. Impacts of cowpea innovation platforms in sustaining TL III project gains in Ghana -- Chapter 13. A cross-case analysis of innovation platform experiences in seven countries in West and East Africa and South Asia -- Chapter 14. Innovation platform for catalyzing access to seed of improved legume varieties to smallholder farmers.-.s
Keywords: Agriculture; Plant biotechnology; Plants -- Development; Plant genetics; Agriculture; Plant Biotechnology; Plant Development; Plant Genetics